Effect of herbicides on weed dynamics and seed yield of indian mustard (Brassica juncea) - SHARMA, O L; JAIN, N K (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during the winters of 1997-2000 at Bikaner (Rajasthan), to study the effect of herbicides on weed dynamics and seed yield ofindhih mustard [Brassica juncea (L.) Czemj. & Cosson]. All the cultural and herbicidal treatments effectively reduced the dry matter of weeds by 26.1-94.4% compared with the weedy check. The highest seed yield (879 kg/ha) and net returns (Rs 7 506/ha) were obtained under weed-free treatment, followed by 2 hand-weedings 30 and 45 days after sowing. Among herbicides, pre-emergence isoproturon @ 0.75 kg/ha recorded significantly higher seed yield (628 kg/ha) and.net returns (Rs 5 390/ha). The highest dose of both the herbicides, ie fluchloralin and isoproturon, at any stage of application had phytotoxic effect on crop.